(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Modern online disputes actively occur on forums, social networks, and messaging platforms. Speech acts in these discussions play a key role, as participants express opinions, emotions, and arguments through them. However, features of online communication-anonymity, rapid message exchange, and the absence of nonverbal cues-often lead to typical errors: incorrect statements, rhetorical questions, excessive emotional expression, and misinterpretation of others’ messages.